Analysis of creative and entrepreneurial project learning in accounting expertise of phase F institution based on project based learning in vocational high school - Larasati, Intan; Sohidin, Sohidin (Institute of Computer Science (IOCS), 2025)
This research aims to (1) analys the implementation of PKK learning phase F Accounting expertise at SMKN 1 Karanganyar, (2) analays the application of the PKK project based learning (PjBL) learning model phase F Accounting expertise. This study is a qualitative study with an analytical study approach. The data sources for this study are from interviews and document studies. Data collection was carried out by means of direct interviews with AKL students in grades XI and XII, PKK teachers, heads of AKL expertise programs, and vice principals for curriculum and analyzing student work proposal documents. The validity technique used is content validity, using a supervisor as an expert. The results of this study are as follows. First, the implementation of PKK learning phase F in AKL expertise has met the characteristics of the PjBL model. Second, the PJBL model syntax has been applied but there are still some things that need to be improved. Third, there is no special policy that distinguishes AKL from other expertise. Fourth, there are several achievements of PKK elements that have not been achieved. Fifth, there is still a lack of innovation in the results of student products.